MULTICULTURAL EDUCATION APPROACH TO PESANTREN IN INDONESIA (ANALYSIS STUDY OF JAMES A. BANK MULTICULUTAL EDUCATION APPROACH) - Made Saihu; Taufik Taufik (STIT AL-AMIN KREO TANGERANG, 2020)
This paper discusses the multicultural education approach to pesantren in Indonesia. Critical studies on critical analysis of James A. Bank's multicultural approach empathy include: content integration, knowledge construction processes, reduction of prejudice, equity pedagogy, which in fact only educates emotional intelligence. If this continues to be manifested, then human intellectual and spiritual intelligence will be empty and the aspiration to instill multicultural understanding is felt to be less than optimal. This study aims to develop James A. Bank's multicultural approach through a study of multicultural approaches to education in Islamic boarding schools in Indonesia. This paper is a literature study with data sources obtained through literature and books on multiculturalism education and education models in Islamic boarding schools. The result of this paper is that the process of planting multicultural values in Islamic boarding schools is carried out through balancing the development of the physical aspects, the development of the intellectual aspects, the development of the aspects, and the development of the spiritual aspects. By balancing these components possessed by humans, the five souls, including the spirit of sincerity, the spirit of simplicity, the spirit of independence, the spirit of ukhuwah Islamiyah, and the spirit of freedom, are well planted, and efforts to create ukhuwwah Islamiyyah (brotherhood due to Islam), ukhuwwah wathaniyyah (brotherhood due to homeland), and ukhuwwah basyaraiyyah (brotherhood due to humanity) are easy to implement.